Innovative Work Behaviour Amid Faculty Shortage: The Role of Idiosyncratic-Deals, Digital Technology and Perceived Leadership Support - Khan, Khalil Nasir; Shah, Dr. Mutahir Hussain; Saddique, Fahad (Journal of Posthumanism, 2025)
This study conceptualizes idiosyncratic deals of Work (I-deals), Innovative Work behaviour (IWB), Digital Technology, and Perceived leadership support grounded in practices detected among private and public universities and the teaching faculty of Pakistan. The current study is based on a quantitative, cross-sectional research design in which data was collected through self-administered questionnaires from 365 faculty members of various public sector universities. The findings suggest that individualized deals and perceived managerial support for innovation foster innovative work behaviour with digitally nurtured mediated paths. This study contributes to the innovation literature by showing that in contrast to the predominantly quantitative prior studies on innovation in higher education institutions, authentic and individualized employment arrangements, technology integration, and supportive leadership are clear contributors to the creativity and innovation of the academic workforce.